Enhancing Adsorption of Dyes onto Clay in Bubble Column Adsorber - Mamdouh M. Nassar; Mohammad S. El-Geundi; Abdulrkib A. Al-Wahbi (Adsorption Science & Technology)
Herein, we studied the adsorption of acid dye onto Yemen natural clay in a bubble column adsorber. In addition, the effect of different parameters such as air flow rate, initial dye concentration and clay mass on the adsorption using clay has been investigated. The external and internal mass transfers were analyzed based on external mass transfer and intra-particle diffusion models. Our results showed that the calculated external mass transfer coefficient increased with the increase in air flow rate and mass of clay, but decreased with the increase in initial dye concentration. For the external mass transfer, different coefficient variables can be correlated by the following dimensionless correlation: Sh/Sc 0.33 = 261.65 (F) 0.165 (C 0 ) −0.743 (m) −0.311 . The intra-particle diffusion coefficient, K P , was found to increase with the increase in air flow rate and initial dye concentration, and with the decrease in the mass of clay. For the intra-particle diffusion, the studied variables can be correlated by the equation K P = X (variable) Y . The results of this study reveal that air flow rate has more influence on increasing the rate of adsorption than the initial dye concentration and mass of clay.